Cation-binding Capacity of Membranes Isolated from Micrococcus lysodeikticus - Cutinelli, C. (1969)
A study was made of H(+), Na(+), K(+), Ca(++), and Mg(++) binding and ion-exchange properties of the plasma-mesosome membrane system isolated from Micrococcus lysodeikticus strain NCTC 2665. Titration curves were obtained on membranes prepared according to the method of M. R. J. Salton and further exposed to pH 4 for 4 hr (membranes-H). The dissociation coefficients and binding capacities were obtained by applying the mass law equation and the plot of G. Schatchard to the data. The membranes-H possess four kinds of dissociable groups with pK 4.96, 4.18, 3.60, and 3.09, respectively, and a total binding capacity of 0.65 meq/g (dry weight). Potentiometric titrations of cations in the presence and in the absence of membranes-H show that cations (Na(+), K(+), Ca(++), and Mg(++)) are bound by the dissociated groups of the membrane. The fall in pH value for bivalent cations is greater than that for monovalent cations. Cations of the same valency produce equal diminutions on pH. Furthermore, ion-exchange tests carried out on membranes saturated with Mg(++) or Na(+) and suspended in a medium containing (45)Ca show that the cations are reversibly bound.